2008
DOI: 10.1214/07-ss032
|View full text |Cite
|
Sign up to set email alerts
|

Sparse sampling: Spatial design for monitoring stream networks

Abstract: Spatial designs for monitoring stream networks, especially ephemeral systems, are typically non-standard, `sparse' and can be very complex, reflecting the complexity of the ecosystem being monitored, the scale of the population, and the competing multiple monitoring objectives. The main purpose of this paper is to present a review of approaches to spatial design to enable informed decisions to be made about developing practical and optimal spatial designs for future monitoring of streams.Comment: Published in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 99 publications
(128 reference statements)
0
29
0
6
Order By: Relevance
“…For a good general review on this topic we refer to Dobbie et al (2008), where also other approaches like stratified sampling, latin square sampling and randomized sampling are reviewed. Basic to the model-based approach is the fact that the spatial observations are modeled as realizations of a random field {Y(x)| x [ X}, where X is the spatial domain under investigation and Y(x) are random variables modeling the observations.…”
Section: Survey Of Model-based Spatial Sampling Designmentioning
confidence: 99%
“…For a good general review on this topic we refer to Dobbie et al (2008), where also other approaches like stratified sampling, latin square sampling and randomized sampling are reviewed. Basic to the model-based approach is the fact that the spatial observations are modeled as realizations of a random field {Y(x)| x [ X}, where X is the spatial domain under investigation and Y(x) are random variables modeling the observations.…”
Section: Survey Of Model-based Spatial Sampling Designmentioning
confidence: 99%
“…There are inherent trade-offs between the number of streams or watersheds that can be assessed and the sampling intensity within each stream (Dobbie et al 2008), especially because time and personnel resources were both identified by stewardship staff as major limitations to monitoring efforts. Ultimately, within-reach sampling intensities may be affected by the extent of each First Nation's territory and their monitoring capacity, which varies among stewardship offices.…”
Section: Broader Sampling Considerationsmentioning
confidence: 99%
“…A monitoring design specifies the resource to be monitored, what will be measured, how it will be measured (i.e., the response design), where it will be monitored (i.e., the survey design), how frequently it will be monitored, and how measurements will be summarized [2]. In this paper I focus on survey design-often called sample design or spatial design [3]-and how best to generate a rigorous, useful, and flexible survey design that specifies where environmental data will be collected. Stehman [2] suggests that a good survey design should be probability-based; have a low and known estimated variance; be spatially-balanced, simple, and cost-effective; and have flexibility as a key characteristic because of real-world, practical challenges that environmental monitoring programs inevitably face [4].…”
Section: Introductionmentioning
confidence: 99%